Effects of endolymphatic sac decompression surgery on endolymphatic hydrops. (December 2013) - Fukushima, Munehisa; Kitahara, Tadashi; Horii, Arata; Inohara, Hidenori
Abstract Conclusions: The present findings suggest that complete control of vertigo after endolymphatic sac decompression surgery (ESDS) does not always depend on improved vestibular function or reduced endolymphatic hydrops. Vertigo control is, however, associated with hearing stability. Objective: Among surgical treatments for intractable Meniere's disease, ESDS is performed to preserve and improve inner ear function. We examined the correlation between changes in vertigo frequency and neuro-otologic function to understand the condition of the inner ear in patients whose vertigo was completely controlled after undergoing ESDS. Methods: This was a retrospective cross-tabulation study. Between 1997 and 2001, we treated 52 patients with intractable vertigo using ESDS and followed the patients regularly for 2 years. Postoperatively we evaluated and recorded changes in vertigo attack frequency, maximum slow phase eye velocity, worst hearing level, and glycerol test results according to modified American Academy of Otolaryngology–Head and Neck Surgery 1995 criteria. Results: We found no correlation between vertigo control and vestibular function. There was also no correlation between vertigo control and negative conversion of the glycerol test. There was a significant correlation between vertigo control and hearing control .